PHYSIOLOGICAL EFFECTS OF LAVENDER, ROSEMARY, AND SAGE ESSENTIAL OILS ON THE CARDIOVASCULAR AND RESPIRATORY SYSTEMS - Shirmatova Madinabonu Odiljon kizi; Mukhamedieva Irodakhon Bakhtiyorkhoja Kizi (Innovate Conferences, 2025)
In recent years, research in phytotherapy and aromatherapy has provided growing scientific evidence of the multifaceted physiological effects of essential oils on the human body. The regulation and restoration of cardiovascular and respiratory system functions through natural bioactive compounds have become an important area of modern medical science. Essential oils derived from lavender, rosemary, and sage possess calming, spasmolytic, bronchodilatory, and antioxidant properties. Their ability to influence autonomic regulation via the central nervous system and to maintain normal circulatory and respiratory activity represents a promising direction in both experimental and clinical physiology. Therefore, studying the complex effects of these essential oils on cardiovascular and respiratory systems, as well as determining their preventive and therapeutic potential, is of significant relevance to contemporary physiological and clinical practice.